If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -70 + -20x = -45 + -8x Solving -70 + -20x = -45 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -70 + -20x + 8x = -45 + -8x + 8x Combine like terms: -20x + 8x = -12x -70 + -12x = -45 + -8x + 8x Combine like terms: -8x + 8x = 0 -70 + -12x = -45 + 0 -70 + -12x = -45 Add '70' to each side of the equation. -70 + 70 + -12x = -45 + 70 Combine like terms: -70 + 70 = 0 0 + -12x = -45 + 70 -12x = -45 + 70 Combine like terms: -45 + 70 = 25 -12x = 25 Divide each side by '-12'. x = -2.083333333 Simplifying x = -2.083333333
| f(x)=x^2-12+42 | | 7(y-3)=4y-29 | | 2x+50=70 | | 4-2(x+3)=-7x+(-2) | | 6x-3+2=8x+7-10 | | -88=5(-2x-8)-6x | | 8s=96 | | x+2(2x+3)-1=0.5(4x+28) | | -2b+5-3+b=b-4b+1-10 | | 2r-4r=4-r | | 5x+40=2 | | -(k-3)+3k=-25+6k | | 4a-12=2a+6 | | 1-3x^2-4x^3=0 | | 470+2x=330+4x | | 18x+27y=10 | | -7(3x+6)+x=-6x-4(6x+8) | | 7(x+10)=140 | | x/2-8.5=15 | | f(x)=-6+3x | | 3x-7=72 | | (x+2)-(-3x-8)= | | 24x^2+20x-24= | | -16+2d=5+4d | | 3x^2-265=3x^2-10x+6.25 | | -8d+18-9+15d= | | 2+3(t+7)=6t-2+2t | | .7g-4=10 | | -2=10-2.5x | | 8v-4v=144-64 | | 11-14b+10= | | s(t)=-16t^2+50t+4 |